RETRACTED: Monitoring of the state of atmospheric air on the example of the city of Omsk - Shustova Ulyana; Korchevskaya Yulia; Trotsenko Irina; Shelest Sergey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001